Antioxidant Activity and Anti-Nutritional Factors in Acacia Nilotica Gum: Life Sciences-Allied Sciences - Kazi Layla Khaled; Rukshana Irani (International Journal of Life Science and Pharma Research, 2022)
The rapidly growing civilization and economy need the judicious usage of floral and faunal heritage. Acacia nilotica (Family: Fabaceae) is a beneficial plant species and each part of it exhibits numerous biological and pharmacological effects. The gum exudates of Acacia nilotica trees are underutilized plant products that can be explored for their potential as a therapeutic and curative agent. Its nutritional composition, interaction with anti-nutritional factors and antioxidants can determine its utility as a food. The present investigation was aimed to estimate the anti-nutritional factors and antioxidant activity of Acacia nilotica gum. It also focused on establishing a relationship of the obtained data with the ethnomedicinal and pharmacological properties claimed in the literature. The analysis was carried out using standard methods and protocols involving spectrophotometric and gravimetric principlesR. The anti- nutritional components like tannin, trypsin inhibitor, phytate, oxalate, total saponin, steroidal saponins, alkaloid content of Acacia nilotica gum was found to be 0.2369±0.0354 g tannic acid equivalent/100 g, 0.0108±0.0037 TIU/mg, 156.3333±9.4516 mg/100 g, 132.5±28.3152mg/100 g, 12.7183±6.7788 mg diosgenin equivalent /g, 0.0705±0.01 mg diosgenin equivalent /g, 0.1333±0.0577 g/100 g respectively. The amounts of total phenols and flavonoids was determined to be 8.0033±2.7211 mg of gallic acid equivalent/g sample, 0.0458±0.0186 mg quercetin equivalent /g sample respectively with a significant DPPH Scavenging activity. The results indicate that the quantity of anti-nutritional factors in gum is within the range of the contents of anti-nutritional factors found in commonly consumed foods. The substantial presence of phenol, flavonoids and DPPH activity in the gum indicates the presence of high antioxidant properties. The presence of anti-nutritional factors and antioxidants in favourable levels can impart diverse physiological responses. The present study concluded that Acacia nilotica gum can be used as a nutritious food commodity with a plethora of recuperative activities.